Effect of a Fortified Dairy-Based Drink on Micronutrient Status, Growth, and Cognitive Development of Nigerian Toddlers- A Dose-Response Study - Senbanjo, Idowu Odunayo; Owolabi, Adedotun J.; Oshikoya, Kazeem Adeola; Hageman, Jeske H. J.; Adeniyi, Yetunde; Samuel, Folake; Melse-Boonstra, Alida; Schaafsma, Anne (Frontiers in Nutrition, 2022)
Malnutrition results in a high prevalence of stunting, underweight, and micronutrient deficiencies. This study investigated the effect of a multi-nutrient fortified dairy-based drink on micronutrient status, growth, and cognitive development in malnourished [height-for-age z-score (HAZ) and/or weight-for-age z-score (WAZ) < -1 SD and >−3 SD] Nigerian toddlers (n = 184, 1–3 years). The product was provided in different daily amounts (200, 400, or 600 ml) for 6 months. At baseline and endline, venous blood and urine samples were collected to determine micronutrient status. Bodyweight, height, waist, and head circumference were measured, and corresponding Z-scores were calculated. The Bayley-III Screening Test was used to classify the cognitive development of the children. In a modified per-protocol (PP) population, the highest prevalence's of micronutrient deficiencies were found for vitamin A (35.5%) and selenium (17.9%). At endline, there were no significant improvements in iodine, zinc, vitamin B12, and folate status in any of the three groups. Regarding vitamin D status (25OHD), consumption of 600 and 400 ml resulted in an improved status as compared to baseline, and in a difference between the 600- and 200-ml groups. Consumption of 600 ml also increased vitamin A and selenium status as compared to baseline, but no differences were found between groups. Within the groups, WAZ, weight-for-height z-score (WHZ), and BMI-for-age z-score (BAZ) improved, but without differences between the groups. For HAZ, only the 600 ml group showed improvement within the group, but it was not different between groups. For the absolute weight, height, and head circumference only trends for differences between groups were indicated. Cognition results did not differ between the groups. Within groups, all showed a decline in the per cent of competent children for receptive language. To study the effects of a nutritional intervention on linear growth and cognition, a longer study duration might be necessary. Regarding the improvement of micronutrient status, 600 ml of fortified dairy-based drink seems most effective. Clinical Trial Registration: https://clinicaltrials.gov/ct2/show/NCT03411590?term=NCT03411590.&draw=2&rank=1, identifier: NCT03411590.